Ideology and class conflict in Jamaica : the politics of rebellion - Bakan, Abigail B. (Abigail Bess), 1954- (McGill-Queen's University Press, 1990)
In each rebellion, two ideological themes re-appear with remarkable tenacity. Bakan demonstrates the existence of "the religious idiom," an ideological current which uses Biblical teaching to reinforce and justify the struggle for greater rights. Also, Bakan shows that there is a belief in the justice and benevolence of the British Crown. Jamaican labourers have repeatedly looked to the Crown as a protector of lower-class interests as opposed to the interests of the local authorities, even when these authorities are appointed by the Crown. Bakan's synthesis of the Gramscian concepts of "willed" and "organic" ideology and of Rudé's notions of "inherent" and "derived" ideology move Ideology and Class Conflict in Jamaica beyond mere historical description. She describes Jamaican resistance as an aspect of willed ideology, with features that are both derived from middle- and ruling-class influences and inherent in the traditions of slaves, peasants, and workers. Each of the rebellions also contains an important organic element which influenced, and in turn was influenced by, the willed ideological aspects.